Biodegradable electrospun scaffolds for skin wound regeneration: a review - Mendizabal-Velazquez, Alondra; Granados-Romero, Juan José; Montalvo-Hernández, Jorge; Vázquez-González, Juan C.; Palacios-Rodríguez, Patricia M.; González-Martínez, Itaty C.; Brito-Brito, Nicolás R.; Abundez-Pliego, Ana L.; Valderrama-Treviño, Alan I.; Barrera-Mera, Baltazar (International Journal of Research in Medical Sciences, 2023)
Over the years, skin substitutes have been sought as an alternative for the treatment of different pathologies. In this article, we focus on describing the use of different biodegradable nanofibrillar polymers as skin substitutes in the treatment of acute and chronic wounds, obtained by the electrospinning technique. Electrospinning is a tissue engineering technique used to generate nanofibers of different polymers that are characterized by having a high surface area, low molecular weight, high resistance rates, and nanoporosity, which is why they are particularly interesting for biomedicine, with potential applicability. in the replacement of skin and tubular organs. In this context, the skin created by tissue engineering has high expectations of application in the study of treatment of skin wounds.